Transforming the Quality of Santri Based on Pesantren Culture - Halid, Ahmad; Sulaiman; Muhammad Ilyas; Maria Ulfa; Luluk Mashluchah; Muhammad Yasaruddin bin Yassir (Edukasia Islamika : Jurnal Pendidikan Islam, 2024)
Transforming the quality of santri based on pesantren culture examines how pesantren knowledge about beliefs, values, and norms can be used to improve the quality of education for students. The purpose of this research is a critical exploration related to the transformation of the quality of students based on pesantren culture in Pesantren Nurul Islam (Nuris) Antirogo Jember, Pesantren al-Azhar Tegalbesar Kaliwates Jember and Pesantren Assunniyah Kencong Jember. The research method used descriptive qualitative by collecting data through observation, interviews and documentation. Data analysis model Milles and Huberman, checking the validity of the data using data triangulation. The theory in this study uses the opinion of KH. Hasyim Asy'ari, Gray model, Byrk model quality, Paul Mott model, Cameron and Quinn model, Edward Sallis, Crosby and Tony Bush. The result of the research is the transformation of the quality of students based on quality pesantren culture in Nuris, al-Azhar and Assunniyah Jember Islamic Boarding Schools is divided into two, namely academic quality and non-academic quality. The academic quality of these three boarding schools are (1) students can read the YellowIslamic classic Book, (2) have noble character, (3) master the sciences taught in the pesantren. (4) realizing the importance of spirituality and religion in life, (5) excellent report card scores and (6) having special skills prepared in pesantren. Meanwhile, the non-academic quality of santri in these three boarding schools are: First, the quality of santri is measured by the activeness of santri in studying at the boarding school. Second, the quality of santri is seen from the principle of the usefulness of the knowledge obtained while studying at the pesantren.